Prediction models for individual-level healthcare costs associated with cardiovascular events in the UK - Zhou, J; Wu, R; Williams, C; Emberson, J; Reith, C; Keech, A; Robson, J; Wilkinson, K; Armitage, J; Gray, A; Simes, J; Baigent, C; et al. (Springer, 2023)
Objectives: To develop prediction models for the individual-level impacts of cardiovascular events on UK healthcare costs.